2020
DOI: 10.1128/mra.00665-20
|View full text |Cite
|
Sign up to set email alerts
|

Draft Genome Sequences of Six Strains of Lactococcus lactis (Phylum Firmicutes ), Spanning the Seeds of Cucumis sativus L. (Cucumber), Cucumis melo L. (Cantaloupe), and Cucurbita pepo var. turbinate (Acorn Squash)

Abstract: We announce the draft genome sequences of six strains of Lactococcus lactis (EKM101L, EKM102L, EKM201L, EKM203L, EKM501L, and EKM502L). These candidate plant probiotics were isolated from surface-sterilized seeds of Cucumis sativus L. (cucumber), Cucumis melo L. (cantaloupe), and Cucurbita pepo var. turbinate (acorn squash). They display beneficial activities, including biocontrol.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…L. lactis isolates were cultivated from the aerial root mucilage of Sierra Mixe, a Mexican highland landrace of maize from Oaxaca, proximal to several landraces in this study; Sierra Mixe was shown to have significant nitrogen fixation activity ( Higdon et al, 2020 ). L. lactis isolates from cucurbit seeds were shown to secrete auxin and acetoin, solubilize phosphate and have antifungal activities ( Khalaf and Raizada, 2016 , 2018 , 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…L. lactis isolates were cultivated from the aerial root mucilage of Sierra Mixe, a Mexican highland landrace of maize from Oaxaca, proximal to several landraces in this study; Sierra Mixe was shown to have significant nitrogen fixation activity ( Higdon et al, 2020 ). L. lactis isolates from cucurbit seeds were shown to secrete auxin and acetoin, solubilize phosphate and have antifungal activities ( Khalaf and Raizada, 2016 , 2018 , 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Probiotic species that can alter the gut microbiota are included in a variety of pharmacological regimens for the treatment of human and animal diseases. Probiotics are living commensal bacteria with anticarcinogenic and immune-modulating capabilities that boost human immunity (Fooladi et al, 2015;Khalaf & Raizada, 2020). Other lactic acid bacteria (LAB) can impact immune responses if fed in sufficient proportions (El-Baz et al, 2021;Fooladi et al, 2015).…”
Section: Introductionmentioning
confidence: 99%